The role of relative hyperprolactinemia in the genesis of the оvarian follicular cysts development - Т. Ф Татарчук; Н. В. Косей; О. В. Занько; О. Г. Околох (Publishing House TRILIST, 2020)
Follicular ovarian cysts (FOC) today occur in 25-30% in the structure of all tumors and tumor-like formations in gynecological practice and tend to increase. The study presents the results of using four different treatment regimens for FOC treatment in patients aged 18 to 42 years. Group I (n = 46) consisted of women with uncomplicated course of FOC who received complex hormonal therapy for 3 months. Group II (n = 49) patients who received monotherapy with a special extract of the Vitex Agnus Castus BNO 1095 (Cyclodynon®) for 6 months. Group III (n = 47) - patients who received a combination of hormone therapy (3 months) and BNO 1095 (6 months). Group IV (n = 35) - patients who did not receive drug therapy (expectant tactics + lifestyle modification). The highest efficacy in relation to the elimination of FOC and the stability of the result during the year was observed in patients of group III who received complex hormone therapy + BNO 1095 extract. Elimination of FOC in 100% of patients within 3 months with a result of more than 95% of patients during the year. Complex hormonal therapy without the use of BNO 1095 (group I) also showed a rather high efficiency with respect to the regression of FOC, but the result was not stable. During the year, relapses in the formation of FOC were observed in 37% of patients. Monotherapy BNO 1095 (group II) demonstrated the efficacy of resorption of the cyst for 6 months in 87% of cases, with the result being preserved for over a year in almost 80% of patients. Active observation (group IV) showed fairly low efficacy: after a year of observation FOC had more of 63% of patients. The average prolactin level in the study groups was higher than the reference values. During the observation period, prolactin levels in all groups except the control group decreased statistically. After 12 months of follow-up, in the group of women who received a combination of hormone therapy with Cyclodynon®, steady normalization of steroid hormones, estradiol and progesterone, was observed, which is explained by the restoration of the biphasic menstrual cycle in most women of this group. The study confirms the role of functional hyperprolactinemia in the development of FOC and the advisability of prescribing Cyclodynon® in their treatment regimen both in combination with hormone therapy and monotherapy (if there are have contraindications to hormone therapy or reproductive plans).